1996
DOI: 10.1148/radiology.201.1.8816539
|View full text |Cite
|
Sign up to set email alerts
|

Common bile duct obstruction due to malignancy: treatment with plastic versus metal stents.

Abstract: Use of self-expanding metal stents appears to show substantial benefits for patients and to be cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
3
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(139 citation statements)
references
References 0 publications
10
119
3
7
Order By: Relevance
“…The complication rates appear to be similar to those in previous studies using either plastic stents or metallic expandable stents (22,23). These complications may have resulted from transhepatic drainage instead of the stent itself.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The complication rates appear to be similar to those in previous studies using either plastic stents or metallic expandable stents (22,23). These complications may have resulted from transhepatic drainage instead of the stent itself.…”
Section: Discussionsupporting
confidence: 82%
“…In plastic stent insertion by the percutaneous approach, large-bore devices with a diameter of 10∼14 Fr can be used (22). Insertion of large prostheses, however, increases the trauma to the patient, particularly during transhepatic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A plastic stent may also be used according to the preference of each facility with available equipment and techniques. (Grade 2, evidence level C) Statement: For the palliative treatment of distal bile duct obstruction, several randomized trials comparing plastic stent (PS) and uncovered SEMS showed that uncovered SEMS has significantly longer term patency than PS [100][101][102]. These trials also showed the lower complication rate of SEMS than PS.…”
Section: Cq15: Which Type Of Biliary Stent Is Appropriate For Unresecmentioning
confidence: 99%
“…The most frequent localization for the infiltrating type of cholangiocarcinoma is proximal or middle bile duct, where the use of percutaneous approach of prothesis implantation is preferable compared to endoscopic route. According to our experience and to published studies, 3,4 the patency of metal stents lasts longer in comparison with plastic drains. Moreover, tolerance and patient compliance are higher when using a metallic stent.…”
Section: Introductionmentioning
confidence: 66%
“…Median time from the first percutaneous intervention to the successful implantation of metal stent was 44 days, and the average number of percutaneous sessions totalled 5.2 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). This depended on the favorable effect of percutaneous drainage (for at least 2 weeks, with substantial improvement of laboratory tests), of the technique and the necessary time for histological confirmation of malignant stenosis.…”
Section: Resultsmentioning
confidence: 99%